2020
DOI: 10.2169/internalmedicine.3695-19
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 Deficiency Anemia and Polyneuropathy Due to Chronic Radiation Enteritis

Abstract: A 62-year-old Japanese woman developed numbness of the extremities and megaloblastic anemia. She had undergone total abdominal hysterectomy, whole-pelvis radiation therapy and chemotherapy for gynecological cancer 10 years before. Chronic abdominal pain, diarrhea and intermittent small-bowel obstruction had afflicted her for a long time. We diagnosed her with vitamin B12 deficiency anemia and polyneuropathy due to chronic radiation enteritis causing malabsorption. Vitamin B12 injections improved her numbness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
3
2
0
1
Order By: Relevance
“…At the same time, this study also found that there was no correlation between HEP and EPO levels, which was consistent with our previous research results [10][11][12]. This is because HEP is an important factor leading to anemia in tumors or other chronic inflammatory diseases.…”
Section: Discusssupporting
confidence: 92%
See 2 more Smart Citations
“…At the same time, this study also found that there was no correlation between HEP and EPO levels, which was consistent with our previous research results [10][11][12]. This is because HEP is an important factor leading to anemia in tumors or other chronic inflammatory diseases.…”
Section: Discusssupporting
confidence: 92%
“…At the same time, the nutritional indicators ALB and PA were both significantly lower after radiotherapy than before, indicating that radiotherapy can also deteriorate the nutritional status of patients. In addition, ALB and PA were both positively correlated with HB, suggesting that the deterioration of nutritional status could cause or aggravate anemia, which was also consistent with literature [6,7].…”
Section: Discusssupporting
confidence: 90%
See 1 more Smart Citation
“…Patients with diabetes mellitus and hyperglycemia are at an increased risk of developing CRC and are associated with a poor prognosis; a positive correlation between altered glycolytic metabolism and tumor recurrence was observed in patients after preoperative chemotherapy [16][17][18][19]. One of the common chemotherapeutic side effects was enteric malabsorption, which led to colonic retention of dietary sugars and accounts for high glucose (HG) delivery through the apical route to CRC cells [20,21]. Despite the indisputable roles of increased glucose uptake and altered glucose metabolism in tumor progression, the underlying mechanisms of glucose-mediated chemoresistance remain incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with diabetes mellitus and hyperglycemia are at increased risk of developing CRC, and a positive correlation was observed between altered glycolytic metabolism and tumor recurrence in patients after preoperative chemotherapy [16][17][18]. In addition, enteric malabsorption, as a chemotherapeutic side effect, leads to colonic retention of dietary sugars, which accounts for an alternative route for high glucose delivery to CRC cells [19,20]. Despite the irrefutable roles of high glucose uptake and altered glucose metabolism contributing to tumor growth, the underlying mechanisms of glucose-mediated tumor chemoresistance remain incompletely understood.…”
Section: Introductionmentioning
confidence: 99%